Enhance marketing performance trough heritage, sincerity and quality commitment - Feby Evelyna; Kabul Trifiyanto (International Journal of Applied Finance and Business Studies, 2025)
This study investigates the influence of brand authenticity dimensions on marketing performance in Central Java's batik industry. Despite UNESCO's recognition of batik as an Intangible Cultural Heritage and its strong export growth, batik entrepreneurs face challenges in developing effective marketing strategies amid increasing competition. Using a quantitative approach, we examined how three dimensions of brand authenticity—heritage, sincerity, and quality commitment—impact the marketing performance of batik enterprises. Data were collected from batik entrepreneurs in Central Java using a five-point Likert scale questionnaire and analyzed through SEM-PLS. Results revealed that the sincerity dimension significantly influences marketing performance, while heritage and quality commitment showed positive but non-significant relationships. These findings suggest that while all dimensions contribute to marketing performance, transparency, honesty, and genuine adherence to traditional values are particularly crucial for batik enterprises. The non-significant impact of heritage may indicate that cultural connections have become a baseline expectation rather than a differentiating factor in this industry. Similarly, quality commitment appears to function more as a necessary condition than a performance driver. This research contributes to brand authenticity theory by highlighting dimension-specific impacts in indigenous product contexts and offers practical guidance for batik entrepreneurs seeking to leverage authenticity for competitive advantage in markets increasingly favoring authentic, unique, and sustainable products.